O39: THE HISTOPATHOLOGICAL AND MOLECULAR FEATURES OF BREAST CARCINOMA WITH HIGH-GRADE TUMOUR BUDDING. (27th April 2021) - Lloyd, A; Ryan, E; Boland, M; Medani, S; Elwahab, Abd; Malone, C; Sweeney, K; Barry, K; McLaughlin, R; Lowery, A; Kerin, M
Abstract: Background: Tumour budding (TB) is an adverse histological feature in many cancers. It is thought to represent epithelial-to-mesenchymal transition, a key step in the metastatic process. The role of TB in breast carcinoma (BC) remains unclear. Aim: To investigate the relationship between TB and other histological and molecular features of BC. Method: A systematic search was performed to identify studies that compared features of BC based on the presence or absence of high-grade TB. Dichotomous variables were pooled as odds ratios (OR) using the Cochran–Mantel–Haenszel method. Quality assessment of the included studies was performed using the Newcastle-Ottawa scale (NOS). Result: Seven studies with a total of 1040 patients (high grade TB n=519, 49.9%; low grade TB n=521, 50.1%) were included. A moderate- to high-risk of bias was noted. The median NOS was 7 (range 6-8). High-grade TB was significantly associated with lymph node involvement (OR 2.28, 95% c.i. 1.74 to 2.98, P <0.001) and lymphovascular invasion (OR 3.08, 95% c.i. 2.13 to 4.47, P <0.001). Regarding molecular subtypes, there was an increased likelihood of high-grade TB in oestrogen- (OR 1.66, 95% c.i. 1.21 to 2.29, P =0.002) and progesterone-receptor positive (OR 1.68, 95% c.i. 1.10 to 2.59, P =0.02) tumours. In contrast triple negative breast cancer had a reduced incidence of high-grade TB (OR 0.46, 95% c.i. 0.30 to 0.72, P =0.0006). Conclusion: High-grade TB is enriched in hormone-positive BC and is associated with known adverse prognostic variables. TB may offer new insights into the metastatic processes of luminal BC. Take-home message: High-grade TB is enriched in hormone-positive BC and is associated with known adverse prognostic variables. TB may offer new insights into the metastatic processes of luminal BC.